2014
DOI: 10.1159/000358803
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of the Extent of Lymph Node Micrometastasis in Undifferentiated-Type Early Gastric Cancer

Abstract: Objective: Lymph node (LN) metastasis is one of the most important prognostic factors for undifferentiated-type early gastric cancer (EGC). The aim of this study was to examine expansion of micrometastasis in regional LNs to clarify the importance of lymphadenectomy for undifferentiated-type EGC. Methods: Clinicopathological features of 307 patients with undifferentiated-type EGC who underwent gastrectomy with lymphadenectomy between 1997 and 2010 at the Department of Surgical Oncology, Osaka City University, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
(35 reference statements)
3
16
0
Order By: Relevance
“…The risk of lymph node metastasis is known to be higher in EGC with undifferentiatedtype histology compared to intestinal type EGC due to lymphovascular invasion, which was estimated to be 14% in a study of post-gastrectomy patients [51] . Moreover, micrometastasis which is associated with worse disease-free survival was reported as 13.3% in the EGC with undifferentiated-type histology [52] . However, there is no definitive method to detect lymph node metastasis accurately before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of lymph node metastasis is known to be higher in EGC with undifferentiatedtype histology compared to intestinal type EGC due to lymphovascular invasion, which was estimated to be 14% in a study of post-gastrectomy patients [51] . Moreover, micrometastasis which is associated with worse disease-free survival was reported as 13.3% in the EGC with undifferentiated-type histology [52] . However, there is no definitive method to detect lymph node metastasis accurately before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the diffuse form of GC are directly triggered by bioactive in ammation of the gastric mucosa [34,35]. Diffuse forms are normally prevalent in younger patients with an elevated risk of LN metastasis compared with intestinal types [36][37][38]. Our study demonstrated that Lauren classi cation was an independent risk index for LN metastasis and diffuse type was related with elevated risk of LN metastasis relative to the intestinal form.…”
Section: Discussionmentioning
confidence: 65%
“…The relationship between tumour invasion depth, lymph node metastasis, distant metastasis and prognosis in diffuse GC also showed the same trends. Studies have shown that lymph node metastasis is an independent factor in the prognosis of patients [20][21] . Patients with node-negative disease have a higher 5-year survival rate than that of patients with lymph node metastasis, and the survival time of patients with lymph node metastasis decreases with an increase in the number of metastatic lymph nodes.…”
Section: Discussionmentioning
confidence: 99%